Optical Coherence Tomography Findings of Retinal Folds in Nanophthalmos - F. Nilüfer Yalçındağ; Huban Atilla; Figen Batıoğlu (Case Reports in Ophthalmological Medicine)
Aim. To report the optical coherence tomography (OCT) findings in three members of the same family with nanophthalmos associated with elevated papillomacular retinal fold. Methods. Complete ophthalmic examination as well as ultrasonography and OCT was performed in all patients. Results. Axial lengths ranged from 16.75 mm to 17.48 mm and refractive errors ranged from +17.50 D to +20.50 D. Main fundus findings were the hyperopic crowded, cupless optic disc, and retinal fold through papillomacular region. Macular OCT scans revealed retinal fold with normal retinal pigment epithelium and choriocapillaris. Interpretation. It is presumed that the retinal folds in nanophthalmos result from a redundancy of the retinal layer caused by retarded growth of the scleral, choroidal, and retinal pigment epithelial layers. The anatomic information provided by the current study is consistent with this thesis.